2015
DOI: 10.1039/c5py00921a
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous copper(0) mediated reversible deactivation radical polymerization of 2-hydroxyethyl acrylate

Abstract: a Reversible deactivation radical polymerization (RDRP) of 2-hydroxyethyl acrylate in D2O with Cu(0) wire mediation and with two-step Cu(0) in situ mediation was investigated. The concentration of active species on the Cu(0) surface, which was influenced by Cu(0) type (wire or particle), polymer chain length, and activator and deactivator concentration, was the key factor in understanding the formation of insoluble gel with Cu(0) wire and/or a high molecular weight (MW) shoulder observed in the polymer molar m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…It is important to stress that a chloride salt was preferred to a bromide salt to avoid unsatisfactory halogen‐exchange throughout polymerization . Although the quantity of salt present in the reaction medium is greater than in previous reports, the speed of the polymerization was not affected (as opposed to previous investigations), as full monomer conversions could still be attained within 30 min. In order to probe the potential of the technique to afford good control to both lower and higher molecular weights (co)polymers, a range of targeted DP n s were attempted ( DP n = 10–160, Table ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…It is important to stress that a chloride salt was preferred to a bromide salt to avoid unsatisfactory halogen‐exchange throughout polymerization . Although the quantity of salt present in the reaction medium is greater than in previous reports, the speed of the polymerization was not affected (as opposed to previous investigations), as full monomer conversions could still be attained within 30 min. In order to probe the potential of the technique to afford good control to both lower and higher molecular weights (co)polymers, a range of targeted DP n s were attempted ( DP n = 10–160, Table ).…”
Section: Resultsmentioning
confidence: 80%
“…The large dispersity value indicates that termination events remain prevalent in the halogen exchange system, which can be attributed to inefficient deactivation due to dissociation of the deactivating complex ([Cu II (PMDETA)Cl]Cl) . It had been suggested that the addition of external halide salts can improve the control over the polymerization, by reducing the extent of complex dissociation, as previously reported . Hence the polymerization of PEGMA 475 ([I]:[M]:[PMDETA]:[CuCl]= 1:40:0.6:1.1, 20% v/v monomer in water) was conducted with an external halide source (NaCl,) utilizing previously reported concentrations (0.3 m ) .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Monomers such as 2-ethylhexyl acrylate (EHA), ,,, benzyl acrylate (BzA), and 2-methoxyethyl acrylate (MEA) , have successfully produced the corresponding polyacrylate under SET-LRP conditions. The list is so broad that it ranges from hydrophobic such as adamantly acrylate (ADA), lauryl acrylate (LA), and octadecyl acrylate (OA) to hydrophilic and water-soluble acrylates such as 2-hydroxyethyl acrylate (HEA), , ,, 2-acryloyloxyethyl phosphorylchlorine (APC), di­(ethylene glycol) 2-ethylhexyl ether acrylate (DEGEEA), and oligo­(ethylene oxide) methyl ether acrylate (OEGMEA). ,, Monomers such as solketal acrylate ((2,2-dimethyl-1,3-dioxolan-4-yl)­methyl acrylate) (SA), glycidyl acrylate (GA), o -nitrobenzyl acrylate (NBA), dithiophenolmaleimide acrylate (DMMA), acrylic acid 3-trimethylsilanyl-prop-2-ynyl ester (TMSPA), N , N -dimethylaminoethyl acrylate (DMAEA), pentaerythritol triacrylate (PETA), and 2-(acryloyloxy)­ethyl 3,4-bis­(2-phenylethynyl)­benzoate (ABPB) have been polymerized by SET-LRP leading to functionalized polymers. Our laboratory also reported the polymerization of several semifluorinated acrylates such as 1 H ,1 H ,2 H ,2 H -perfluorooctyl acrylate (PFOA), 2,2,3,3,4,4,4-heptafluorobutyl acrylate (HFBA), 1,1,1,3,3,3-hexafluoroisopropyl acrylate (HFIPA), and 1 H ,1 H ,5 H -octafluoropentyl acrylate (OFPA), whereas others reported that SET-LRP is also compatible with sugar-containing acrylates such as glucose acrylate (GlcA), mannose acrylate (ManA), fucose acrylate (FucA), and 2-[( d -glycosamin-2- N -yl)­carbonil]­oxyethyl acrylate (HEAGI) …”
Section: Brief Overview and Developments On Set-lrpmentioning
confidence: 99%
“…Reversible deactivation radical polymerization (RDRP) [1,2,3,4,5,6,7] including initiator-transfer agent-terminator (Iniferter) [8,9,10,11], nitroxide-mediated polymerization (NMP) [12,13,14,15,16,17,18], atom transfer radical polymerization (ATRP) or metal-catalyzed living radical polymerization [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43] and reversible addition−fragmentation chain transfer polymerization (RAFT) [44,45,46,47,48,49,50,51,52,53,54,55] has been used to design and synthesize various polymeric structure and architectures extensively. Among those methods, ATRP is the most widely used method and has been used to produce different topological polymers, such as star, brush, block and hyperbranched polymers [56,57,58,59].…”
Section: Introductionmentioning
confidence: 99%